PENGGUNAAN MEDIA SOSIAL ONLINE DALAM BERDAKWAH: KEMUNGKINAAN ADOPSI DAN STRATEGI PEMANFAATANNYA - Nurdin Nurdin (Komunitas Dosen Dakwah Institut Agama Islam Negeri (IAIN) Palu, 2012)
This study focuses on online social media adoption and usage for dakwah purposes. The author argues that social media should be adopted and used by da'i in delivering their dakwah because most of Indonesian are muslim and most of them have also adopted and used social media such as Facebook, blog, mailing list, and Youtube. The number of social media users in Indonesia has significantly increase recently which is included in five highest social media user countries. This study also found that social media has been adopted and used by a number of da'i and muslim groups to deliver Islamic message to communities. However, the used of social media has yet to achieve a maximum level that benefits all muslim communities. Future studies are required to understand the issue.